Adoption of conservative agricultural practices among rural Chinese farmers - Qing Yang; Abdullah Al Mamun; Farzana Naznen; Muhammad Mehedi Masud (Humanities & Social Sciences Communications, 2024)
Abstract Excessive use of agrochemicals and the misuse of natural resources severely degrade farmlands. In addition to organic farming, conservative agricultural practices are one of the most viable methods for preventing environmental deterioration. Its adoption has remained relatively modest in developing countries as farmers rely exclusively on synthetic inputs to attain high yields and economic returns. Therefore, this study focuses on the factors that influence farmers’ intention and adoption of conservative agricultural practices. This study extended the Value-Belief-Norm (VBN) framework with a new construct (green trust), and empirically evaluated all fundamental VBN components with their chained relationships among constructs. This cross-sectional study collected quantitative data from 349 farmers using structured interviews. The partial least squares structural equation modeling (PLS-SEM) method was used to statistically evaluate the relationship between the constructs. The analysis demonstrates that both biospheric and altruistic values have a positive impact on the new environmental paradigm, which, in turn, has a significant impact on people’s awareness of consequences and personal norms. Although awareness of consequences had a substantial positive influence on the ascription of responsibilities, it was demonstrated to have a statistically insignificant impact on personal norms. In parallel, the ascription of responsibility had a strong impact on personal norms, which, in turn, positively influenced the intention towards conservative agricultural practices. Remarkably, green trust was found to have the greatest effect on farmers’ intentions. Finally, farmers’ actual adoption was significantly influenced by their intention. The findings of this study will contribute to the strengthening of relevant factors among farmers that may enhance eco-friendly farming practices, develop solutions for regulating the protected utilization of natural resources, and effectively prevent environmental deterioration caused by hazardous agrochemicals. The study will also provide guidance to government regulators and other social organizations in the formulation of effective laws, policies, and strategies for the mass adoption of conservation practices and restoration of agricultural ecosystem balance.